2023
DOI: 10.1530/joe-22-0111
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome: a core regulator of metabolism

Abstract: The human body is inhabited by numerous bacteria, fungi, and viruses, and each part has a unique microbial community structure. The gastrointestinal tract harbors approximately 100 trillion strains comprising more than 1,000 bacterial species that maintain symbiotic relationships with the host. The gut microbiota consists mainly of the phyla Firmicutes, Bacteroidetes, Proteobacteria, and Actinobacteria. Of these, Firmicutes and Bacteroidetes constitute 70–90% of the total abundance. Gut microbiota utilize nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 197 publications
(197 reference statements)
0
18
0
Order By: Relevance
“…Therefore, disruption of these functions, known as dysbiosis, can cause metabolic disorders including the development of T2D (Figure ). 8 Recently, the prospective association of gut microbiota with T2D or glycemic traits has been investigated in several European and Chinese, large population-based cohorts. These studies identified certain bacterial features of fecal samples that are associated negatively or positively with T2D.…”
Section: See Accompanying Article On Page 477mentioning
confidence: 99%
“…Therefore, disruption of these functions, known as dysbiosis, can cause metabolic disorders including the development of T2D (Figure ). 8 Recently, the prospective association of gut microbiota with T2D or glycemic traits has been investigated in several European and Chinese, large population-based cohorts. These studies identified certain bacterial features of fecal samples that are associated negatively or positively with T2D.…”
Section: See Accompanying Article On Page 477mentioning
confidence: 99%
“…These products promote gut health by improving the integrity of the mucosal barrier and mucus production and reducing inflammation. They can cross the blood-brain barrier and participate in maintaining its integrity, preserving brain homeostasis [43,63,64]. In addition, many studies have demonstrated that stress can modulate microbiota compositions and reduce the richness and diversity of the gut microbiota [65][66][67].…”
Section: Gut-brain Axis Role In Physiological and Pathological Statesmentioning
confidence: 99%
“…The gastrointestinal microbiome is a vital controller of host nervous system and the brain as a command center, therefore directly governing several glands and organs of the human body, responsible for vast number of conditions and diseases (Fujisaka et al., 2023). The gut microbiome accommodates abundant number of genes and contributes in essence with more genetic diversity, versatility, and resilience than the human host genome (Sharon et al., 2022), whereas mammalian microbiome constitution is controlled by ecological influences rather than by host genetics (Rothschild et al., 2022).…”
Section: The Gut Microbiotamentioning
confidence: 99%